Mechanical vapour compression refrigeration system: Review part 1: Environment challenge - Raid, Ahmed Mahmood; Omar, M. Ali; Noor, M.M. (Zielona Góra: Uniwersytet Zielonogórski)
In Australia and others developed countries, concerns about global warming have increased, and these concerns influence the use of refrigerants as working fluids in mechanical vapour compression refrigeration systems. One of the most important aspects of refrigerant selection is to reduce its impact on the environment and the ozone layer.
Keywords: alternative refrigerants; mixture refrigerants; vapour compression refrigeration system; ozone depletion potential (ODP); global worming potential (GWP); R507A refrigerant; natural refrigerant; R-718 (water/steam)